Radiation attenuation properties of novel glass system using experimental and Geant4 simulation. (October 2022) - Aladailah, M.W.; Tashlykov, O.L.; Shirmanov, I.A.; Strugov, E.D.; Sayyed, M.I.; Marashdeh, Mohammad W.; Elsafi, M.; Al-Maaitah, A.F.
Abstract: The purpose of this study is to estimate the radiation shielding capacities of glass systems with the system of 45 SiO2 – 15 CaO – (40-x) BaO – (x) ZnO (where x = 0, 10, 20, 30, and 40 wt%). The mass attenuation coefficients, μ/ρ of these glasses have been calculated by using XCOM software and Geant4 simulation toolkit tool in the energy range of 0.0595 MeV–1.410 MeV. The experimental data have been carried out using a narrow beam using the NaI(Tl) scintillation detector at the energies of (59.52 KeV) 241 Am, (661.66 keV) 137 Cs, (1173.23, 1332.50 keV) 60 Co, 152 Eu(121.78, 244.69, 344.28, 964.13, 1408.1 KeV). The MAC calculated results were compared with the experimental values. There have been good agreements noticed. The other attenuation parameters were calculated such as the linear attenuation coefficient (μ ), half value layer (HVL), mean free path (MFP) and the effective atomic number (Zeff) . The attenuation results of this glass system were compared with some recently published commercial glasses, and the results showed that this glass system is important in the radiation protection field. Highlights: Gamma-ray shielding properties of SiO2 –CaO–BaO– ZnO have been studied. The μm results were measured, and compared with Geant 4 and WinXCom values. The SCBZ40 with 40 wt% ZnO has the best effectiveness shielding against gamma photons. The data can be used in radiation protection and other fields.